Perencanaan Pembelajaran Proyek Penguatan Profil Pelajar Pancasila pada Sekolah Penggerak - Anwar, Rosyida Nurul (Institut Agama Islam Sunan Giri Ponorogo, 2023)
The purpose of this study was to find out how the learning planning of the project supported the profile of Pancasila students in penggerak schools. The research method uses a descriptive qualitative approach. The research location was conducted at the Batch 2 driving schools in Madiun Regency at the early childhood education level, with as many as 11 academic units. Data collection techniques using observation, interviews, and documentation. The results of the study show that the learning plan for the project to strengthen the profile of Pancasila students in the academic unit at the early childhood education level is; first, time management in organizing learning; second, forming a team of project facilitators; third, compiling project teaching modules; fourth, designing a strategy for reporting project results. The project aims to strengthen the profile of Pancasila students into learning that benefits students so that they become lifelong learners.